2016
DOI: 10.1186/s12894-016-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the complications of traditional 12 cores transrectal prostate biopsy with image fusion guided transperineal prostate biopsy

Abstract: BackgroundTo compare the complications of traditional transrectal (TR) prostate biopsy and image fusion guided transperineal (TP) prostate biopsy in our center.MethodsTwo hundred and fourty-two patients who underwent prostate biopsy from August 2014 to January 2015were reviewed. Among them, 144 patients underwent systematic 12-core transrectal ultrasonography (TRUS) guided prostate biopsy (TR approach) while 98 patients underwent free-hand transperineal targeted biopsy with TRUS and multi-parameter magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
(20 reference statements)
1
27
0
3
Order By: Relevance
“…Additionally, targeted biopsy may reduce the infection rate as a result of the lower number of cores taken [29]. In a recent study comparing transrectal sysPbx with transperineal targeted biopsy, Huang et al [30] reported a significantly lower infection rate in the transperineal cohort. In the present study, which focused on determining the benefit of fusPbx, sysPbx and comPbx, we therefore combined the standard transrectal with the transperineal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, targeted biopsy may reduce the infection rate as a result of the lower number of cores taken [29]. In a recent study comparing transrectal sysPbx with transperineal targeted biopsy, Huang et al [30] reported a significantly lower infection rate in the transperineal cohort. In the present study, which focused on determining the benefit of fusPbx, sysPbx and comPbx, we therefore combined the standard transrectal with the transperineal approach.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to complications, with TR prostate biopsy, the incidence rate of infection and rectal bleeding is higher [16] and lesions located in the anterior part of the prostate, particularly in high volume prostates, might be missed. With TP prostate biopsy, on the other hand, the incidence of perineal swelling is higher [16], and, usually for ensuring more patient comfort, it needs to be done in general anesthesia, holding its own risks.…”
Section: Introductionmentioning
confidence: 99%
“…With TP prostate biopsy, on the other hand, the incidence of perineal swelling is higher [16], and, usually for ensuring more patient comfort, it needs to be done in general anesthesia, holding its own risks.…”
Section: Introductionmentioning
confidence: 99%
“…Since this study was a retrospective analysis, it was subject to data collection restrictions and did not provide information about postoperative complications. However, current studies have shown that the incidence rates of complications did not differ significantly among the 8‐ to 12‐core biopsy methods . Therefore, we believe that if there is evidence supporting statistically significant differences in the PCa and csPCa detection rates, we should use the biopsy method with the higher detection rate.…”
Section: Discussionmentioning
confidence: 78%
“…However, current studies have shown that the incidence rates of complications did not differ significantly among the 8-to 12-core biopsy methods. 20,27 Therefore, we believe that if there is evidence supporting statistically significant differences in the PCa and csPCa detection rates, we should use the biopsy method with the higher detection rate. This work was a retrospective study, and all of the information used was based on historical data from a US workstation.…”
Section: Discussionmentioning
confidence: 99%